Influence of Interethnic Contact on Interethnic Attitudes of Malay and Chinese- Malaysian University Students in Malaysia - Tamam, Ezhar (A Publication of the Pacific and Asian Communication Association, 2009)
Although interethnic contact is expected to contribute towards positive interethnic attitudes, it is not clear how much interethnic contact contributes towards interethnic attitudes in contexts where there is “no real majority,” such as Malaysia. The data for this study come from a self-administered survey involving 379 Malay and 381 Chinese- Malaysian university students in large public universities. As predicted, interethnic contact contributes significantly towards regarding different ethnic groups positively. Although the effect is small, it holds for both ethnic groups. The present findings improve the generalizability of the predictions of contact theory regarding interethnic attitude, which have been mainly observed in studies conducted in the Western world, as well as extend the theory beyond the majority-minority and host-immigrant contexts.